BTCC Referral Program: Earn While You Share - BTCC Referral Code (22677866) (2025)
Once you're in, turn the tables—become a referrer! Access your unique code via the "Referral" tab in your account: Share your link/code/QR on social media, forums, or with friends. Earn 25% of their fees forever (up to 60% in affiliate mode). No cap on referrals—scale your earnings passively. It's a win-win: Your friends get the BTCCUSD perks, and you build a revenue stream.